Application of Information and Communication Technology (ICT) for Agricultural Transformation in Nepal - Khatri, Bishnu Bahadur; Timsina, Tirtha Raj; Rijal, Nirajan (Ganeshman Darpan, 2024)
Information and communication technology (ICT) is said to be the better catalyst for empowering farmers to ensure from field to prosperity for rural development. Despite being fundamental source of livelihood for two-third of total population, Nepalese agriculture suffered from multiple challenges such as conventional practices, inappropriate technological adoption and fragmentation of productive land and so on which are hindering its progress. This paper tries to emphasize the need of agricultural transformation through the integration of ICT that eventually contribute for rural development in Nepal. This is a review-based research paper consists of quantitative approach and employs a descriptive research design based on a rigorous review of scholarly publications, government plans and other documents along with online database related to the use of ICT in agriculture. The findings highlight the declining contribution of agriculture to the national GDP as a result of the prevalence of subsistence farming with ineffective technical accessibility and the potential of ICT to address these challenges. The study concludes with a discussion on the role of ICT in empowering farmers, improving productivity, and contributing to rural development through specific ICT initiatives such as mobile apps for agriculture-related information and advisory services. The study as a whole highlight the potential of information and communication technology (ICT) as a pivotal tool for driving transformation in the agricultural sector and fostering rural development in Nepal. The study suggests to integrate ICT in agriculture transformation to empower Nepalese farmers and boost agricultural productivity for rural development.